Childhood Posterior Reversible Encephalopathy Syndrome (PRES) in Resource Limited Settings: Addressing Diagnostic and Therapeutic Hurdles-A Case Report - Bipesh Kumar Shah; Sadmarg Thakur; Prajjwol Luitel; Roshan Gaire (Case Reports in Pediatrics)
Posterior reversible encephalopathy syndrome (PRES) is a condition that manifests with symptoms like altered mental status, seizures, vision impairment, and vasogenic edema primarily affecting the occipital and parietal lobes, with occasional involvement of the frontoparietal regions. We report a case of a 10 year old girl who arrived at the pediatric emergency department with generalized swelling, dark-colored urine, and two days of seizures following recent throat infection. Her blood pressure consistently exceeded the 95th percentile by +12 mm Hg, indicating stage 2 hypertension. A computed tomography (CT) scan showed hypodensities (edema) in the parieto-occipital white matter, consistent with PRES. Due to limited resources, magnetic resonance imaging (MRI) could not be performed. The patient was treated symptomatically with levetiracetam for seizures and furosemide and amlodipine for hypertension. By the fifth day of hospitalization, the patient experienced significant improvement, with a return to normal appetite, urine color, and neurological function. Early diagnosis contributed to her full recovery. Physicians in resource limited settings should have high degree of suspicion of pediatric PRES and perform detailed history taking, examination, laboratory investigations and imaging (whenever available) for management of pediatric PRES.